THE EFFECT OF FREQUENCY OF GIVING PGPR (Plant Growth Promoting Rhizobacteria)AND MEDIA TYPES ON GROWTH AND PRODUCTION OF RED ONION (Allium Cepa L.) IN LOW LANDS - Addien Syam Fil A W P; Pramono Hadi, Srie juli Rachmawatie (PROSEDING, 2022)
This study aims to determine the effect of the frequency of PGPR and types of media on the growth and production of Red Onion plants in the lowlands, this study was conducted from February to April 2019, in Tegalmulyo RT 03 RW 01 Nusukan, Banjarsari, Surakarta, Central Java. This study uses a factorial method with a basic pattern of Completely Randomized Design (CRD) consisting of two treatment factors and repeated three times. The first treatment factor, the frequency of giving PGPR (P) consisting of 3 types (P1 = Without PGPR, P2 = Giving PGPR 1 week 1 time, and P3 = = Giving PGPR 1 week 2 times). The second treatment factor, Types of Planting Media (M) which consists of three types (M1 = type of soil media, M2 = type of sand media, M3 = type of soil and sand media (50:50)). The observations can be concluded that the frequency of giving the best PGPR is 1 week 2 times because the results obtained from plant height, wet stover weight, dry stover weight, number of leaves, number of tubers and tuber weight. better than without PGPR and the frequency of giving PGPR 1 week 1 time. The best type of planting media is the soil from the parameters of plant height, weight of bulbs, number of bulbs, weight of wet stover, number of leaves and weight of dry stover. The interaction between the treatment of the frequency of PGPR and the type of media has a very significant effect on the weight of wet stover, tuber weight and number of tubers, while significantly influencing the number of leaves and not significantly different on plant height and dry stover weight. Combination of P3M1 treatment (Frequency of Giving PGPR 1 week 2 times and type of soil media) gives the best production on all parameters . and Combination of P1M2 treatment(Without PGPR and sand media) give the low production on all parameters Keywords: PGPR, red onion,type of media, plants, production